2002
DOI: 10.1111/j.1651-2227.2002.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant improves oxygenation in infants and children with pneumonia and acute respiratory distress syndrome

Abstract: Aim: Pneumonia in childhood may be associated with surfactant dysfunction and severe acute respiratory distress syndrome (ARDS). The aim of this study was to investigate the effects of surfactant treatment on oxygenation in 8 infants (age range: 1 mo to 13 y) with severe respiratory failure owing to viral, bacterial or Pneumocystis Carinii pneumonia. Methods and results: Instillation of a modified porcine surfactant (Curosurf®) improved gas exchange immediately. Median paO2/FiO2 increased from 66 to 140mmHg (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…16,17 Epithelial cell injury by inflammatory mediators can result in increased permeability of the microvasculature leading to leakage of protein and fluid which can also inactivate surfactant. 13,16,18 Out of the 25 patients in our study that required a repeat course of surfactant therapy seven (28%) had an acute infectious process, three (12%) had pulmonary hemorrhage and 21 had worsening BPD (84%) that led to their surfactant dysfunction. Six (24%) of these patients had more than one cause for their respiratory deterioration.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…16,17 Epithelial cell injury by inflammatory mediators can result in increased permeability of the microvasculature leading to leakage of protein and fluid which can also inactivate surfactant. 13,16,18 Out of the 25 patients in our study that required a repeat course of surfactant therapy seven (28%) had an acute infectious process, three (12%) had pulmonary hemorrhage and 21 had worsening BPD (84%) that led to their surfactant dysfunction. Six (24%) of these patients had more than one cause for their respiratory deterioration.…”
Section: Discussionmentioning
confidence: 90%
“…18,19 Bissinger et al 10 described three patients with secondary surfactant deficiency or postsurfactant slump that responded to repeat courses of surfactant. At our institution, we found that 20% of ELBW infants diagnosis with RDS at birth received repeat surfactant replacement therapy in the second to sixth week of life to treat postsurfactant slump or respiratory failure associated with presumed secondary surfactant deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of clinical studies have reported benefits following the instillation of exogenous surfactants to term infants, children, or adults with ALI/ARDS or related acute respiratory failure [25,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] (Table 4). However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation).…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…Studies of surfactant therapy in children and adults with ALI/ARDS show positive results in a number of case reports or relatively small pilot trials [120,121,[124][125][126][127][128]. However, particularly in adults, controlled clinical trials have been less successful.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…60 Neonatal pneumonia Pneumonia in children and newborn infants may be associated with surfactant dysfunction and acute RDS. [61][62][63][64][65][66] There are studies involving a small number of neonates who have been treated with rescue surfactant replacement for sepsis and pneumonia that have shown improved gas exchange compared with no surfactant treatment. 61,63,64,67 -69 Verlato et al 70 used the 'exogenous' tracing approach with an endotracheal administration of 13 C-labeled DPPC to study surfactant kinetics in full term with pneumonia, and in preterms with RDS.…”
Section: Surfactant Status Of Preterm Infants Recovering From Rdsmentioning
confidence: 99%